The Use of Grape By-Products as a Feed Additive Enhances the Oxidative Stability of Rabbit Meat - Silvia Carta; Riccardo Chessa; Roberto Rubattu; Anna Nudda; Gianni Battacone (Veterinary Sciences)
The use of agro-industrial by-products in livestock nutrition is of increased interest to the feed industry. Some of the by-products are rich in bioactive compounds that could lead to an increase in the quality of animal meat products. This study aimed to evaluate the effects of dietary incorporation of grape pomace (GP), a by-product rich in polyphenols, on growth and on the oxidation status and the fatty acid profile of rabbit meat. Forty-eight male rabbits (Oryctolagus cuniculus) (aged 55 ± 3 d and ca 2.3 kg) divided into three groups of 16 were used in the trial. The rabbits were housed in pairs in wire-mesh cages (26 × 46 × 35 cm) giving n = 8 for each diet treatment. The first group was fed a basal diet (CTR) (ca 18% protein and ca 4% fat), the second was given a basal diet supplemented with 5 g GP per head per day (low-GP) and the third group was fed a basal diet supplemented with 10 g GP per head per day (high-GP). The trial lasted three weeks, and the animals were weighed weekly. The rabbits were slaughtered, and the weight and the pH of the carcasses was measured immediately after slaughter and after 24 h of cooling at 4 °C. The pH of the stomach and cecum was measured. A sample of Longissimus Dorsi (LD) was collected and stored at −80 °C for the analysis of proximate composition, thiobarbituric acid reactive substances (TBARs) and fatty acid profile (FA). The diet did not influence the growth or the pH of the stomach and cecum of the rabbits. The chemical composition of the meat was similar in all groups, with a mean protein of 22.3% and fat of 0.95%. The fatty acid profiles of the LD were not influenced by the diet, and the most abundant FAs were C16:0, C18:2n6 and C18:1c9. Feeding GP to the rabbits gave a linear decrease of TBARs in the meat, indicating a reduction in oxidative stress. The TBARs’ reduction was 60% in the meat of the rabbits given high-GP compared to CTR. In conclusion, GP could be used in rabbit diets without any negative influence on meat quality but with an increase in oxidation stability that could enhance meat shelf-life.